REKONDISI KINERJA OPERASI FIXED BED GASIFIER SEKAM PADI PT. NATIONAL CHAMPIGNON - Bambang Suwondo Rahardjo (Badan Pengkajian dan Penerapan Teknologi, 2010)
All this time, PT Natcham’s gasifier only be used for synthetic gas production asfuel of 400 kW gas engine power generation for the mushroom industry’selectricity needs while energy crisis. From now on, the application anddevelopment of biomass gasification technology is focused on synthetic gasproduction to be processed furthermore from gas to liquid (GTL) throughFischer–Tropsch synthesis process. H2+CO contained in syngas product is low(average 20% of total producer gas) with H2/CO ratio = 0.30–0,35. Producedsynthetic gas composition more and less equal to the design maker of Peako –China that is feasible to be utilized as fuel for 400 kW gas engine powergeneration, but not meet yet specification requirements of syngas composition asgas feeding for Fischer–Tropsch synthesis process (Gas–To–Liquid, GTL).Installation of O2 and steam injection system inside gasifier necessary to improvesyngas quality, all at once N2 content decreasing in the syngas, with the result ofH2/CO ratio >1 that will improve liquid product.Kata kunci: fixed–bed gasifier, gasification, rice husk, synthetic gas